Helicobacter pylori Peptidoglycan Modifications Confer Lysozyme Resistance and Contribute to Survival in the Host - Wang, Ge (American Society of Microbiology, 2012)
The prominent host muramidase lysozyme cleaves bacterial peptidoglycan (PG), and the enzyme is abundant in mucosal secretions. The lytic enzyme susceptibility of Gram-negative bacteria and mechanisms they use to thwart lytic enzyme activity are poorly studied. We previously characterized a Helicobacter pylori PG modification enzyme, an N-deacetylase (PgdA) involved in lysozyme resistance. In this study, another PG modification enzyme, a putative PG O-acetyltransferase (PatA), was identified. Mass spectral analysis of the purified PG demonstrated that a patA strain contained a greatly reduced amount of acetylated muropeptides, indicating a role for PatA in H. pylori PG O-acetylation. The PG modification mutant strains (pgdA, patA, or pgdA patA) were more susceptible to lysozyme killing than the parent, but this assay required high lysozyme levels (up to 50 mg/ml). However, addition of host lactoferrin conferred lysozyme sensitivity to H. pylori, at physiologically relevant concentrations of both host components (3 mg/ml lactoferrin plus 0.3 mg/ml lysozyme). The pgdA patA double mutant strain was far more susceptible to lysozyme/lactoferrin killing than the parent. Peptidoglycan purified from a pgdA patA mutant was five times more sensitive to lysozyme than PG from the parent strain, while PG from both single mutants displayed intermediate sensitivity. Both sensitivity assays for whole cells and for purified PGs indicated that the modifications mediated by PgdA and PatA have a synergistic effect, conferring lysozyme tolerance. In a mouse infection model, significant colonization deficiency was observed for the double mutant at 3 weeks postinoculation. The results show that PG modifications affect the survival of a Gram-negative pathogen. Importance Pathogenic bacteria evade host antibacterial enzymes by a variety of mechanisms, which include resisting lytic enzymes abundant in the host. Enzymatic modifications to peptidoglycan (PG, the site of action of lysozyme) are a known mechanism used by Gram-positive bacteria to protect against host lysozyme attack. However, Gram-negative bacteria contain a thin layer of PG and a recalcitrant outer membrane permeability barrier to resist lysis, so molecular modifications to cell wall structure in order to combat lysis remain largely unstudied. Here we show that two Helicobacter pylori PG modification enzymes (PgdA and PatA) confer a clear protective advantage to a Gram-negative bacterium. They protect the bacterium from lytic enzyme degradation, albeit via different PG modification activities. Many pathogens are Gram negative, so some would be expected to have a similar cell wall-modifying strategy. Understanding such strategies may be useful for combating pathogen growth.